Ambiguity and equity premium in production economies - Mohammad R. Jahan-Parvar; Hening Liu (The University of Manchester, Manchester Business School, 2011)
We propose a novel one-sector stochastic growth model, where producitivity growth follows a Markov-switching process with two regimes, and where households have generalized recursive smooth ambiguity preferences. The adopted class of preferences permits a three-way separation of risk aversion, ambiguity aversion, and the attitude toward intertemporal substitution. Ambiguity averse agents are ambiguous about the probability distribution of productivity growth. We show that in the absence of ambiguity aversion, the presence of a persistent high productivity regime combined with the elasticity of intertemporal substitution being greater than unity cannot generate a sizable risk premium. With a moderate coefficient of relative risk aversion, our model with ambiguity aversion can account for the low volatility of consumption growth observed in the data, and produce a high and volatile equity premium and a low and smooth risk-free rate. In addition, this model is able to generate, albeit weak, long horizon predictability in equity returns.
Keywords: C61; D81; G11; G12; 330; Ambiguity; Equity premium; Markov switching; Production economy; Smooth ambiguity; CAPM; Risikoprämie; Risikoaversion; Organisationale Ambidextrie; Markovscher Prozess